Shifting of Physicochemical and Biological Characteristics of Coffee Roasting Under Ultrasound-Assisted Extraction - Duangjai, Acharaporn; Saokaew, Surasak; Goh, Bey-Hing; Phisalprapa, Pochamana (Frontiers in Nutrition, 2021)
Ultrasound-assisted extraction (UAE) is an effective tool for extraction of natural antioxidants. Thus, differentially roasted Arabica-coffee beans known as light (LC), medium (MC), and dark coffee (DC) were prepared and extracted under influence of UAE. Following that, they were examined specifically on theirs physicochemical and biological characteristics; nutritional values, pH, °Brix, antioxidant activities, polyphenol content, caffeine, and chlorogenic-acid levels. Various parameters such as extraction temperatures (20, 40, and 80°C) and extraction times (5, 10, and 20 min) were examined. DC extract was less acidic than those on MC and LC extracts. LC showed higher moisture content than the MC and DC (1.56%, 1.3% and 0.92%, respectively). MC displayed the highest polyphenol content as well as potent antioxidant activity. Caffeine and chlorogenic acid contents trend to decrease during roasting. The maximum caffeine level was found in MC at 80°C for 5 min (27.65 mg/g extract). The highest chlorogenic acid content was in LC at 80°C for 10 min (16.67 mg/g extract). The caffeine and chlorogenic acid contents were related to the polyphenol content and depended on the roasting and extraction conditions. These results suggest that the UAE at various temperature and extraction time-period may alter the physicochemical and biological characteristics of different coffee roasts.